Inscriptions of Sanationes from Sanctuaries of god Asclepius. Miraculous recoveries of rheuma diseases - G. Squillace (PAGEPress Publications, 2011)
Inscriptions of Sanationes from Sanctuaries of god Asclepius, testifying to the gratitude of patients to the divinity, present a situation, albeit fragmentary, of main diseases which physicians thought incurable or hardly curable. Sterility, calvities, worms, paralysis, as well as clinical disorders caused by rheuma appear, along with gout/podagra, in many inscriptions too. To counter them, patients asked for the intervention of Asclepius